REALIZING THE LEGAL CERTAINTY OF CALCULATING FINES BUSINESS COMPETITION LAW - Disemadi, Hari Sutra; Roisah, Kholis; Prananingtyas, Paramita (Tadulako Law Review, 2019)
The Business Competition Supervisory Commission (KPPU) by the Business Competition Law (Law Number 5 Year 1999) has been given the authority to impose sanctions in the form of administrative measures, namely the imposition of administrative fines. The amount is very clearly regulated in the Business Competition Law, which is the lower limit and the upper limit. In fact, prior to the implementation of guidelines for calculating fines, many KPPU’s decisions deviated from the amount of sanctions that have been regulated in the Business Competition Law. Therefore, that will raise questions about the quality of the KPPU’s decision. Even worse, if the public or business actors no longer trust KPPU, because KPPU acts unfairly against other business actors. Not fair, by looking at the disparity in determining the amount of fines imposed. To minimize the foregoing, the issuance of guidelines for calculating fines is expected to overcome the disparity problem in imposing fines on the Reported Party. The issuance of this guideline does not in fact intend to limit the space and independence of the KPPU but will instead assist the KPPU’s tasks.